TOTAL CHOLESTEROL LEVELS IN TRADITIONAL COFFEE DRINKERS DUSUN SEMBUNG DAYE NARMADA LOMBOK DISTRICT WEST - Maruni Wiwin Diarti; Iswari Pauzi; Siti Rif’ah Sabariah (Jurnal Kesehatan Prima, 2016)
Abstract : Traditional coffee is one of the widely-consumed beverages Lombok Island community, one in Hamlet Sembung Daye. Coffee contains cafestol and kahweol substances that can raise cholesterol levels in the blood. This research is a descriptive study that aims to describe how the total cholesterol levels in the traditional coffee drinkers in the hamlet Sembung Daye Narmada District of West Lombok regency that the examination carried out using test methods strip. Data collected in the form of total cholesterol at 83 traditional coffee drinkers in the hamlet Sembung Daye Subdistrict Naramada West Lombok regency. The results showed the average total cholesterol level in males was 225 mg / dl and in women is 217 mg / dl. The conclusion of this study is total cholesterol levels in the traditional coffee drinkers in the hamlet Sembung Daye Narmada District of West Lombok district is more than the normal value.